2014
DOI: 10.1017/s1049023x14001186
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with the Intention of Health Care Personnel to Respond to a Disaster

Abstract: The intention to respond was influenced primarily by normative and control factors. The intent of nurses to respond to a future PHE was influenced most by the control factors, whereas the intent of other HCP was shaped more by the normative factors. Health care educators can bolster the normative and control factors through education by focusing on team building and knowledge related to accessing supplies and support needed to respond when a disaster occurs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The finding is similar with findings from Korea and United States of America. 32 , 37 In contrast, the finding from Korea revealed that subjective norms were not associated with nursing intention to care. 22 This could be due to those with normative control intend to execute more beneficial behaviors.…”
Section: Discussionmentioning
confidence: 86%
“…The finding is similar with findings from Korea and United States of America. 32 , 37 In contrast, the finding from Korea revealed that subjective norms were not associated with nursing intention to care. 22 This could be due to those with normative control intend to execute more beneficial behaviors.…”
Section: Discussionmentioning
confidence: 86%
“…In this model, overwork can be explained as a job‐related variable, while department, felt anxious and fear also can be explained as the perceived risk. Besides, nurses who had a higher level of EP were likely to response because of the higher perceived behavioural control (Connor, 2014b; Grimes & Mendias, 2010; Ko et al., 2004). The factor of education level we identified was also in line with previous studies (Basta, Edwards, & Schulte, 2009; Martinese et al., 2009; Seale, Leask, Po, & MacIntyre, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Our study is unique considering both factors affected willingness and interventions to improve it. [45][46][47][48][49] This approach makes more comprehensive vision for researchers in analyzing data. In addition, we used common intervention themes with the HRH framework of the world health organization (WHO).…”
Section: Theme 4 -Leadershipmentioning
confidence: 99%